Pediatric obstructive sleep apnea: Preoperative and neurocognitive considerations for perioperative management. Issue 5 (25th March 2020) - Chandrakantan, Arvind; Musso, Mary F.; Floyd, Thomas; Adler, Adam C.
Abstract: Obstructive sleep apnea (OSA) affects up to 7.5% of the pediatric population and is associated with a variety of behavioral and neurocognitive sequelae. Prompt diagnosis and treatment is critical to halting and potentially reversing these changes. Depending on the severity of the OSA and comorbid conditions, different treatment paradigms can be pursued, each of which has its own unique risk:benefit ratio. Adenotonsillectomy is first‐line recommended surgical treatment for pediatric OSA. However, it carries its own perioperative risks and the decision regarding surgical timing is therefore made in the context of procedural risk versus patient benefit. This article presents the seminal perioperative and neurocognitive risks from pediatric OSA to aid with perioperative management.